Are maximum P wave duration and P wave dispersion a marker of target organ damage in the hypertensive population? - Dagli, N.; Karaca, I.; Yavuzkir, M.; Balin, M.; Arslan, N. (Springer Heidelberg, 2008)
High blood pressure, left ventricular hypertrophy and diastolic dysfunction may cause hemodynamic and morphological changes in the left atrium, consequently instability and heterogeneity in atrial conduction. This is seen as an increase in maximum P wave duration (P-max) and P wave dispersion (PD) on the electrocardiogram (ECG). P wave dispersion on ECG has been encountered as a risk factor for atrial fibrillation (AF). The aim of this study is to examine whether PD and P-max can be used as a non-invasive marker of target organ damage (LVH and diastolic dysfunction) in a hypertensive population. Material and methods The study registered a total of 120 cases (mean age 46.9 +/- 10.6 years; 58 [48.3%] males and 62 [51.7%] females), of whom 60 were patients diagnosed as essential hypertension (group 1), and 60 were healthy individuals, who constituted the control group (group 2). Systolic and diastolic functions of all cases were evaluated by echocardiography, and maximum P wave duration (P-max), and PD was calculated. Results Maximum P wave duration was 91.6 +/- 10.2 ms in group 1, and 64 +/- 10.2 ms in group 2 (p < 0.01), while PD was 56.1 +/- 5.8 ms in group 1, and 30.3 +/- 6.6 ms in group 2 (p < 0.01). Blood pressure, left atrium diameter, DT, IVRT, and E/A ratio, as well as left ventricular mass index increased markedly in group 1. Conclusion High blood pressure, LVH, diastolic dysfunction and increased left atrium diameter and volume shows parallelism in hypertensive cases. These physiopathological changes may cause different and heterogeneous atrial electrical conduction. This led to a marked increase in P-max and PD in our cases. Thus, the results support the hypothesis that PD can be used as a non-invasive marker of target organ damage (LVH and LV diastolic dysfunction) in the hypertension population.
Keywords: hypertension; P wave duration; target organ damage